TINJAUAN YURIDIS TERHADAP PROSES AKUISISI LINTAS NEGARA YANG DILAKUKAN OLEH - EDWARD CHENNADY (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Bismar Nasution2. Mahmul Siregar3. T. Keizerina Devi A Acquisition is a way of expanding the company by way of corporate development involving organizations outside the company. Acquisitions are legal actions by a legal entity or an individual to acquire shares of the Company that result in the transfer of control over the Company. Due to the rapid development of economic globalization led to developments in acquisitions that led to the emergence of cross-border acquisitions. Cross-border Acquisitions are acquisitions made by parties with different nationalities. This thesis will discuss the acquisition process based on the regulation in Indonesia and the change of company status due to cross-border acquisition and prohibition of acquisition implementation.Keywords: Acquisition; Cross-border; Foreign investment.